Anesthetic Management of a Patient with Myasthenia Gravis for Meningioma Surgery - A Case Report - Srivastava, VK; Agrawal, S; Ahmed, M; Sharma, S (Kathmandu University Medical Journal, 2015)
Note: On 26th October, the author 'A. Agrawal' was corrected TO 'S. Agrawal'. Myasthenia gravis is a disease of great challenge to the anesthesiologist, because it affects the neuromuscular junction. Anesthetic management involves either muscle relaxant or non-muscle relaxant techniques. This case report documents the safe use of fentanyl, propofol and sevoflurane combination guided by bispectral index, without the use of muscle relaxants in a patient with myasthenia gravis who presented for meningioma surgery. Kathmandu University Medical Journal Vol.13(1) 2015; 80-82